2011
DOI: 10.1172/jci58056
|View full text |Cite
|
Sign up to set email alerts
|

Deficit of tRNALys modification by Cdkal1 causes the development of type 2 diabetes in mice

Abstract: The worldwide prevalence of type 2 diabetes (T2D), which is caused by a combination of environmental and genetic factors, is increasing. With regard to genetic factors, variations in the gene encoding Cdk5 regulatory associated protein 1-like 1 (Cdkal1) have been associated with an impaired insulin response and increased risk of T2D across different ethnic populations, but the molecular function of this protein has not been characterized. Here, we show that Cdkal1 is a mammalian methylthiotransferase that bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
263
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 217 publications
(280 citation statements)
references
References 46 publications
11
263
2
1
Order By: Relevance
“…Beta cellspecific CDKAL1 knockout mice models suggested that functional loss of CDKAL1 affects the accuracy of protein translation, causing the synthesis of abnormal insulin, which triggers estrogen receptor stress in beta cells. 30,31 The significant association between the SNP rs9472138 (about 73 kb to the transcription start site of VEGFA) and T2D was firstly replicated among Chinese population. Zeggini et al first reported in Caucasian that rs9472138 was associated with T2D in GWAS scan and the first stage validation, but achieved a borderline significant association (P¼0.095) in the second stage validation.…”
Section: Discussionmentioning
confidence: 96%
“…Beta cellspecific CDKAL1 knockout mice models suggested that functional loss of CDKAL1 affects the accuracy of protein translation, causing the synthesis of abnormal insulin, which triggers estrogen receptor stress in beta cells. 30,31 The significant association between the SNP rs9472138 (about 73 kb to the transcription start site of VEGFA) and T2D was firstly replicated among Chinese population. Zeggini et al first reported in Caucasian that rs9472138 was associated with T2D in GWAS scan and the first stage validation, but achieved a borderline significant association (P¼0.095) in the second stage validation.…”
Section: Discussionmentioning
confidence: 96%
“…As Cdk5 regulates insulin secretion [17,18], it is postulated that Cdkal1 may regulate insulin secretion through the regulation of Cdk5 activity. However, Cdkal1 has no ability to interact with Cdk5 activators and no effect on Cdk5 activity [19,20]. The primary structure of Cdkal1 has features of the methylthiotransferase (MTTase) family, a subclass of the large radical AdoMet enzyme superfamily [21].…”
Section: Physiological Functions Of Cdkal1mentioning
confidence: 99%
“…Interestingly, the C-terminal hydrophobic domain exists only in Cdkal1 ( Fig. 2A) and the domain contributes to the localization on the endoplasmic reticulum (ER) [20].…”
Section: Physiological Functions Of Cdkal1mentioning
confidence: 99%
See 2 more Smart Citations